El papel de las redes en la ecomposición territorial y distribución de actividades económicas productivas Caso: distritos de Chalhuahuacho y Haquira, Apurímac - Huillcahuanaco Ccoscco, Nancy Clara (2008)
This article describes some findings in the study on the role of the highway linking Izcuchaca in the development of economic relations in the district of Chalhuahuacho, Apurímac, which creates an unequal exchange for the reconfiguration of the economic factors of production taking place in the area and unleashed a dynamic that has led to uneven across a diverse organization on road construction and mining practice.